2019
DOI: 10.1021/acs.jpclett.9b03196
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Motions of Proteins under Non-native States Evaluated Using Quasielastic Neutron Scattering

Abstract: Characterization of the dynamics of disordered polypeptide chains is required to elucidate the behavior of intrinsically disordered proteins and proteins under non-native states related to the folding process. Here we develop a method using quasielastic neutron scattering, combined with small-angle X-ray scattering and dynamic light scattering, to evaluate segmental motions of proteins as well as diffusion of the entire molecules and local side-chain motions. We apply this method to RNase A under the unfolded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…To date, the QENS method has been used in many studies to characterize the overall picture of protein dynamics 29 . The scope of QENS research is expanding from small single-domain proteins 41,42 to larger and more complex molecular systems 43, 44, , as well as to large-scale conformational changes such as those that occur upon ligand binding 33,46,47 , pressurization 48,49,50 , unfolding 35,51,52,53,54,55 , and fibrillization 34,56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the QENS method has been used in many studies to characterize the overall picture of protein dynamics 29 . The scope of QENS research is expanding from small single-domain proteins 41,42 to larger and more complex molecular systems 43, 44, , as well as to large-scale conformational changes such as those that occur upon ligand binding 33,46,47 , pressurization 48,49,50 , unfolding 35,51,52,53,54,55 , and fibrillization 34,56 .…”
Section: Discussionmentioning
confidence: 99%
“…(B) Temperature dependences of jump-diffusion frequency (τ -1) for KaiC, human hemoglobin (Hb), and α-synuclein (αSyn). QENS data of Hb and αSyn are taken from previous studies33,51 ; activation energies of deoxygenated Hb (deoxy-Hb), CO-bound Hb (CO-Hb), fibrillized αSyn (fib-αSyn), and monomeric αSyn (mon-αSyn) are 5.2 ± 0.3, 5.2 ± 0.3, 3.7 ± 0.7, and 2.6 ± 1.9 kcal mol -1 , respectively. Values given near fitting lines represent the Q10local values estimated for 303 K.…”
mentioning
confidence: 99%
“…Since the convolution of two Lorentzian functions is also a Lorentzian function, fitting the spectra with the equation containing the two Lorentzian functions distinguish the global motions and the local motions. Whereas L global (Q,ω) of well-folded globular proteins contains only the contributions from the diffusive motions as a rigid body, L global (Q, ω) of those containing the disordered regions contains a non-negligible contribution from the segmental motions [15]. In such cases, the QENS spectra can be described as a first approximation that translational and rotational diffusion as a rigid body and the segmental motions are independent of each other, as:…”
Section: Methodsmentioning
confidence: 99%
“…Thus, if the contributions of the diffusive motions of the entire molecules could be estimated, the contributions of the domain/segmental motions should be extracted. We have thus developed an analysis method that can extract motions at the segment/domain level by combining QENS, small-angle X-ray scattering (SAXS), and dynamic light scattering (DLS) measurements and demonstrated its feasibility [15]. The extraction of the segmental motions is critical for the characterization of the IDPs/IDRs.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its energy range, high resolution, high intensity, and high S/N, the state-of-the-art NBS instrument is suitable for studying the dynamics of proteins. Using a time-of-flight, near-backscattering spectrometer (BL02), at the Materials and Life Science Experimental Facility at J-PARC, Japan [ 18 ], Fujiwara and Matsuo et al have published studies [ 19 , 20 , 21 , 22 , 23 , 24 ] on protein solutions, including an experiment with the world’s lowest concentration of α-Synuclein at that time (9.5 mg/mL (~0.95 wt.%)) [ 20 ]. In recent years, Inoue et al [ 25 ] and Nakagawa et al [ 26 ] reported studies on protein dynamics within protein solutions.…”
Section: Introductionmentioning
confidence: 99%